PENGARUH MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA LEMBAGA PENDIDIKAN ISLAM - Zona Hartini Maysyaroh W; Hery Setiyatna (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2026)
This study aims to analyze the effect of human resource management (HRM) on the performance of Islamic educational institutions. HRM is considered a strategic aspect in improving educational quality. This research uses a qualitative approach with a case study method conducted in an Islamic educational institution through interviews, observation, and documentation. Data were analyzed using thematic analysis. The findings show that effective HRM practicesmincluding recruitment, competency development, motivation, and performance evaluation have a positive impact on institutional performance. The improvement is indicated by a 20% increase in teacher productivity, a decrease in absenteeism to 3%, and an 85% increase in work motivation after competency-based and Islamic value training. The integration of Islamic values such as trustworthiness, honesty, and responsibility strengthens a productive and ethical work culture. However, challenges such as budget limitations and resistance to change still exist. The study concludes that strengthening HRM based on Islamic values significantly contributes to improving the performance of Islamic educational institutions